Psychopharmacology in children and adolescents: unmet needs and opportunities: position paper - Cortese, Samuele; Purper-Ouakil, Diane; Apter, Alan; Arango, Celso; Baeza, Inmaculada; Banaschewski, Tobias; Buitelaar, Jan; Castro-Fornieles, Josefina; Coghill, David; Cohen, David; Correll, Christoph U; Grünblatt, Edna; et al. (The lancet. Psychiatry, 2024)
Psychopharmacological treatment is an important component of the multimodal intervention approach to treating mental health conditions in children and adolescents. Currently, there are many unmet needs but also opportunities, alongside possible risks to consider, regarding the pharmacological treatment of mental health conditions in children and adolescents. In this Position Paper, we highlight and address these unmet needs and opportunities, including the perspectives of clinicians and researchers from the European College of Neuropsychopharmacology-Child and Adolescent Network, alongside those of experts by lived experience from national and international associations, via a survey involving 644 participants from 13 countries, and of regulators, through representation from the European Medicines Agency. We present and discuss the evidence base for medications currently used for mental disorders in children and adolescents, medications in the pipeline, opportunities in the development of novel medications, crucial priorities for the conduct of future clinical studies, challenges and opportunities in terms of the regulatory and legislative framework, and innovations in the way research is conducted, reported, and promoted.